2019
DOI: 10.12659/msm.912362
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Depression and Anxiety in Patients with Chronic Urticaria

Abstract: BackgroundChronic urticaria (CU) is a common disease, characterized by the development of wheals, angioedema, or both. CU reduces quality of life and can also cause emotional distress. Studies addressing depression and anxiety in such patients are rare in the literature. The aim of this study was to determine the relationship between urticaria symptoms and depression and anxiety in patients with CU.Material/MethodsThe Hospital Anxiety-Depression Scale (HADS) was used to evaluate depression and anxiety in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 22 publications
6
36
0
8
Order By: Relevance
“…Of these, 35 were excluded for various reasons (Figure 1). Thirteen studies with a total of 3,627 study participants were included in the final meta-analysis (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Data Sources and Selection Processmentioning
confidence: 99%
“…Of these, 35 were excluded for various reasons (Figure 1). Thirteen studies with a total of 3,627 study participants were included in the final meta-analysis (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Data Sources and Selection Processmentioning
confidence: 99%
“…Hergüner et al (16) reported a positive correlation of disease duration and age with anxiety and Depression scores . On the other hand, Tat et al (18) and Engin et al (17) did not find a correlation between disease duration or age with Anxiety and Depression scores. In our study, we found a positive correlation of age with both anxiety and Depression scores and also with anxiety and depression rates.…”
Section: Discussionmentioning
confidence: 89%
“…Engin et al (17) evaluated 73 adult CSU patients and 34 control cases using BDI and found higher levels of depression among patients compared to controls. Similarly, Tat et al (18) compared 50 adult CSU patients and 60 control cases and reported higher levels of depression in the patient group. In their study, Hergüner et al (16) found a higher level of depression among children with CSU compared to control cases.…”
Section: Discussionmentioning
confidence: 97%
“…The extent to which patients' quality of life (QoL) can be affected by CSU has been demonstrated in numerous studies (1,2,(4)(5)(6)(7)(8) and goes beyond effects on skin (e.g. itching), with many patients reporting fatigue, pain, and sleep disturbances.…”
Section: Significancementioning
confidence: 99%
“…itching), with many patients reporting fatigue, pain, and sleep disturbances. Patients also experience a substantial psychological burden; many develop anxiety and depression after diagnosis, which significantly impacts their QoL (6,7,9,10). Patients also report dissatisfaction with their treatment and their relationship with their physician (5,8,11).…”
Section: Significancementioning
confidence: 99%